Age and sex influence social interactions, but not associations, within a killer whale pod. Issue 1953 (30th June 2021) - Weiss, Michael N.; Franks, Daniel W.; Giles, Deborah A.; Youngstrom, Sadie; Wasser, Samuel K.; Balcomb, Kenneth C.; Ellifrit, David K.; Domenici, Paolo; Cant, Michael A.; Ellis, Samuel; Nielsen, Mia L. K.; Grimes, Charli; et al.
Abstract : Social structure is a fundamental aspect of animal populations. In order to understand the function and evolution of animal societies, it is important to quantify how individual attributes, such as age and sex, shape social relationships. Detecting these influences in wild populations under natural conditions can be challenging, especially when social interactions are difficult to observe and broad-scale measures of association are used as a proxy. In this study, we use unoccupied aerial systems to observe association, synchronous surfacing, and physical contact within a pod of southern resident killer whales ( Orcinus orca ) . We show that interactions do not occur randomly between associated individuals, and that interaction types are not interchangeable. While age and sex did not detectably influence association network structure, both interaction networks showed significant social homophily by age and sex, and centrality within the contact network was higher among females and young individuals. These results suggest killer whales exhibit interesting parallels in social bond formation and social life histories with primates and other terrestrial social mammals, and demonstrate how important patterns can be missed when using associations as a proxy for interactions in animal social network studies.